The ESR signals in silk fibroin and wool keratin under both the effect of UV-irradiation and without any external effects and the formation of free radicals - Mamedov, SV; Aktas, B; Cantürk, M; Aksakal, B; Alekperov, V; Bülbül, F; Yilgin, R; Aslanov, RB (ELSEVIER SCI LTD, 2002)
ESR studies have been done on natural and UV-irradiated silk fibroins and wool keratins at the temperature range of -196degreesC to 20degreesC. The intensities of ESR signals obtained from the irradiated samples at -196degreesC remarkably increase with respect to those of natural samples. While the signals mainly consist of triplet peaks at -196degreesC, a doublet arises around the room temperatures. Foe the first time, at room temperature without any external effect the complicated ESR spectra of fibrous proteins (wool keratin and silk fibroin) whose components are as follows have been observed: (1) (for white wool keratin) a central doublet with DeltaH(m) = 1.1 mT and g = 2.0075 DeltaH(m) = 5 mT and g = 2.1911; (2) a wide peak with DeltaH(m) approximate to 66 mT and g approximate to 2.1575 (3) the 'sulfur' peak given in the literature with DeltaH(m) approximate to 2.2 mT and g = 2.0218 (4) the signal witli DeltaH(m) = 0.6 mT and 2.0065, and for silk fibroin. (a) a very wide signal with DeltaH(m) approximate to 70 mT and g approximate to 2.084 (b) a very sharp signal with DeltaH(m) approximate to 1.1 mT and g approximate to 2.01; and (c) relatively narrower signal with DeltaH(m) approximate to 5 mT and g approximate to 2.336. It has been shown by recombination kinetic method that 30-50% of the free radicals formed by UV-irradiation do not undergo recombination Lip to 220degreesC and 150degreesC for silk fibroin and wool keratin, respectively, even they keep their concentration constant for long period of time (weeks, months, even longer). In this article, considering above-mentioned results. the mechanism of signals observed in natural wool keratin and silk fibroin without any external effects is examined. We can briefly explain the role of the subject of the article, by considering fibrous proteins and some applications of the reactions by free radical occurring in these proteins Under the effects of different factors in medicine and biology and the important role of oxidation mid the other kinds of degradations on these processes, as well as the significant applications of ESR investigations oil comprehending the processes by free radical. (C) 2002 Published by Elsevier Science Ltd.
Keywords: silk fibroin; wool keratin; ESR spectrum; doublet; triplet; free radical; Engineering; Materials Science